Modeling the Predictors of Poverty in Agricultural Households in Uganda: Application of Multilevel and Interaction Methods - Habimana, Robert; Tindimwebwa, Kenneth; Okurut, Francis (East African Journal of Business and Economics, 2024)
This study aimed to model the predictors of poverty in agricultural households in Uganda. The study's specific objectives were to examine the effect of individual predictors of poverty and analyze the contribution of community predictors of poverty in agricultural households. The study utilized data from the Uganda National Household Survey (UNHS, 2019/20) obtained from the Uganda Bureau of Statistics. A sample of 13,732 households was randomly selected from the total weighted sample representation of 11.3 million households involved in agricultural activities. A logit model was used in the analysis and estimates were provided using multilevel and interaction methods. Key findings suggest that poverty in agricultural households was positively and significantly influenced by the gender of the household head, marital status of the household head, income stability of the household, age of the household head and livestock ownership. Additionally, regional differences accounted for 17.9 % of the variations in poverty levels in Uganda and understanding such regional differences and their influence on poverty levels can assist policymakers and organizations in designing targeted interventions and policies to reduce poverty levels among households. Such measures can address the specific challenges faced by different regions and promote more equitable development across the country. However, poverty in agricultural households was negatively and significantly influenced by residence status, savings account ownership and household size. Based on the study's findings, the key policy recommendations were that; the government should continue implementing gender-focused interventions to address gender disparities among women empowerment programs that involve access to resources including land, equal access to employment opportunities and equal access to education to reduce poverty among women. Regarding income instabilities in agricultural households due to price fluctuations, the government should empower farmers to form farmer groups where they can collectively increase their bargaining power to avoid price fluctuations.